The Byzantine chronicles of Symeon Magister and Logothete (10th century.) and John Zonaras (12 cent.) in the literatures of the Southern and Eastern Slavs - Leszka, Mirosław; Brzozowska, Zofia (Balcanica Posnaniensia. Acta et studia, 2023)
The article deals with two Byzantine chronicles that were translated into Old Church Slavic in the Middle Ages on the Balkan Peninsula and were subsequently adapted in Rus’, where they served as the base and source of inspiration for indigenous East Slavic historical studies in universal history. It is about the works of Symeon Magister and Logothete, who probably wrote between the reign of Romanus I Lecapenus and the beginning of the reign of Basil II, and the Epitome historiarum of John Zonaras, covering history from the creation of the world to 1118, which is the most comprehensive Byzantine historical work and which, possibly, was completed ca. 1145. The aim of the article is to establish the chronology of the creation of the Old Church Slavic translations of both chronicles and the history of their dissemination in the Slavia Orthodoxa area (with a review of the state of research). The editions of the translations and unpublished manuscript material were examined (its excerpt is presented in the appendix). We were able to establish that the complete translation of the work of Symeon Magister and Logothete is preserved only in the Moldavian historiographical compilation of 1637, while the text of John Zonaras was translated by the Slavs several times and functioned in their literatures in many versions, none of which, however, is complete.